1998
DOI: 10.1038/sj.leu.2401121
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma: a retrospective study of 121 cases

Abstract: Mantle cell lymphoma (MCL) patients represent a difficult problem, sometimes to establish the diagnosis but mostly because of their refractoriness to standard lymphoma treatments. Which treatments to apply and to whom is not yet defined. In this study, we attempted to analyze the clinical features, to identify the major prognostic factors, and to evaluate the outcome of 121 MCL patients treated in our institution between 1979 and 1997. Clinical data, treatment modalities, and International Prognostic Index (IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 36 publications
5
132
3
2
Order By: Relevance
“…The differentiation of MCL from other nonHodgkin's lymphomas of peripheral B-cell type is clinically relevant because patients with MCL usually present a disseminated disease, extranodal involvement, aggressive course, and refractoriness to standard chemotherapy (5). The diagnosis of MCL first relies on morphological and phenotypical cri- teria but may be problematic when these features overlap with other B-cell lymphomas (6 -8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation of MCL from other nonHodgkin's lymphomas of peripheral B-cell type is clinically relevant because patients with MCL usually present a disseminated disease, extranodal involvement, aggressive course, and refractoriness to standard chemotherapy (5). The diagnosis of MCL first relies on morphological and phenotypical cri- teria but may be problematic when these features overlap with other B-cell lymphomas (6 -8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been individualized both in the REAL and in the World Health Organization classifications because it represents a distinct clinical pathological entity with a special aggressive course among small B-cell lymphomas (2,3). It frequently involves lymph node, blood, bone marrow, and spleen (4,5). The neoplastic cells typically exhibit a centrocytic morphology and coexpress pan-B-cell markers CD5 and CD43 but lack CD23 and CD10.…”
mentioning
confidence: 99%
“…Peripheral blood involvement has been previously reported as an independent variable of poor prognosis in patients with MCL (13,14). Previous studies also have reported that an absolute lymphocytosis of at least 10 ϫ 10 9 /L heralds shorter patient survival compared with patients with MCL and that an absolute lymphocyte count of less than 10 ϫ 10 9 /L (4).…”
Section: Discussionmentioning
confidence: 92%
“…MCL accounts for less than 10% of all NHL and occurs in older males [18]. Patients often present with Stage III or IV disease with extension to extranodal sites including peripheral blood, bone marrow, gastrointestinal tract, and Waldeyer's ring [18][19][20].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%